Difficultés dans l’apprentissage du mesurage - Larcher, C.; Séré, M.G.; Journeaux, R. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 1994)
This paper presents the difficulties encountered by students of first University year, when carrying out measurements in order to answer a question concerning the isochronism of oscillations o a simple pendulum. It is based on a case study which concerns students who followed a course about measurement eforhand. The global strategies of these students are described. Then the difficulties encountered are analysed. We distinguish two categories: firstly, the difficulties stepping from relationships between a theoretical approach of modelised objects and an experimental approach of given objects; secondly the difficulties coming from the conzeptualisation of differences between the measured values and the reference value. Eventually, elements of the response built by the students are analysed, particularly by assessing the reinvestment of the notions of statistics studied beforehand.